1995
DOI: 10.1017/s1357729800008456
|View full text |Cite
|
Sign up to set email alerts
|

The responses of growing pigs, of different sex and genotype, to dietary energy and protein

Abstract: Intact male pigs from two nucleus breeding herds (one predominantly Duroc, DM; the other purebred Large Wliite, LM) together with intact male (RM), castrated male (RC) and female (RF) commercial hybrid pigs were given one of two diets, with the same balanced protein (180 or 240 g/kg) at three daily rates, the highest being 'to appetite'. Six replicates of 30 pigs were allocated to these regimes at 40 kg: one replicate was slaughtered immediately to determine initial carcass composition; the remaining pigs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
3
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 8 publications
10
33
3
5
Order By: Relevance
“…In this way an appropriate balance between ideal CP and energy concentrations can be established and the response of the animals to changes in energy or amino acid (AA) supply can be predicted. To achieve our objective, the optimal supply of dietary ideal CP leading to maximum daily rates of PD (PD max ) and the marginal efficiency of body PD (Fuller et al, 1995), i.e., the change in daily PD per unit change in daily ME at restricted intakes (DPD:DME; g/MJ), were considered. A second objective was to establish reliable estimates of energy utilisation in the growing-fattening pig.…”
Section: Introductionmentioning
confidence: 99%
“…In this way an appropriate balance between ideal CP and energy concentrations can be established and the response of the animals to changes in energy or amino acid (AA) supply can be predicted. To achieve our objective, the optimal supply of dietary ideal CP leading to maximum daily rates of PD (PD max ) and the marginal efficiency of body PD (Fuller et al, 1995), i.e., the change in daily PD per unit change in daily ME at restricted intakes (DPD:DME; g/MJ), were considered. A second objective was to establish reliable estimates of energy utilisation in the growing-fattening pig.…”
Section: Introductionmentioning
confidence: 99%
“…resistance while the genetic Topigs turns out to produce animals with high meat quality, according to Fuller et al (1995). Table 3 presents the results for bacon quality parameters, determined using digitally imaged data.…”
Section: Resultsmentioning
confidence: 99%
“…Kyriazakis et al (1995) observed the same net eff iciency in entire male Large White × Landrace and pure Chinese Meishan pigs. Fuller et al (1995) used Duroc, purebred Large White and a commercial hybrid. The re-examination of their data reveals that below PD max the regression line has a common slope, indicating equal efficiency at suboptimal intakes (Sandberg et al, 2005).…”
Section: Discussionmentioning
confidence: 99%